2016
DOI: 10.1155/2016/8293196
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Expression of VEGF and Podoplanin in Uterine Cervical Squamous Intraepithelial Lesions

Abstract: VEGF and podoplanin (PDPN) have been identified as angiogenesis and/or lymphangiogenesis regulators and might be essential to restrict tumor growth, progression, and metastasis. In the present study, we evaluate the association between the expression of these markers and CIN grade. Immunohistochemistry was performed in 234 uterine cervical samples using conventional histologic sections or TMA with the monoclonal antibodies to VEGF (C-1 clone) and podoplanin (D2-40 clone). Positive-staining rates of VEGF in 191… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 34 publications
1
12
0
1
Order By: Relevance
“…Belfort‐Mattos et al . reported that podoplanin expression was negative or limited in the basal area of CIN3 lesions . Low podoplanin expression in tumor cells was correlated with the presence of lymphatic invasion and lymph node metastasis .…”
Section: Discussionmentioning
confidence: 94%
“…Belfort‐Mattos et al . reported that podoplanin expression was negative or limited in the basal area of CIN3 lesions . Low podoplanin expression in tumor cells was correlated with the presence of lymphatic invasion and lymph node metastasis .…”
Section: Discussionmentioning
confidence: 94%
“…Selected samples included 147 cervical biopsies (100 with squamous intraepithelial neoplasia and 47 without neoplasia) which were collected at the Gynecological Disease Prevention Nucleus. Patients were diagnosed by colposcopical and previous histopathological studies, and the absence of neoplasia was confirmed through the cytological and histopathological examination (13). Women with any kind of immunosuppression, diabetes, organ transplantation, or pregnancy were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
“…Conventional histopathological method. Routinely, we prepared the formalin-fixed paraffin-embedded tissue blocks (13), which were cut into 4-μm-thick sections using an AO American optical 820 Rotary microtome (AO Instrument Company, NY, USA). After assembly onto a glass slide, the tissue was deparaffinized in xylene, rehydrated in graded alcohols, and submitted to hematoxylin and eosin (HE) staining followed by sealing with Entellan ® (Merck Millipore, Darmstadt, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Избыточная экспрессия VEGF наблюдается в большинстве опухолей [56]. Имеются данные, что уровень VEGF коррелирует с клиническими и патологическими особенностями опухолевой прогрессии при карциноме шейки матки [57][58][59]. Показано, что VEGF-сигналинг, индуцируемый AT1R, является одним из ключевых регуляторов роста опухоли и опухолевого ангиогенеза не только в опухолевых тканях, но также в тканях организма-хозяина [60].…”
Section: изучение роли апф при плоскоклеточной карциноме шейки маткиunclassified